Civil ceremonies in socialist Czechoslovakia and post-socialist Slovakia - Beňušková, Zuzana (Ethnological studies, 2021)
This book was written with the primary purpose of filling in the information gap in the collection of academic knowledge about non-religious rituals, which are also known as civil ceremonies. This area forms that part of the ritual culture, the history of which is closely related to the four decades of the Communist regime in Slovakia. Through civil ceremonies following the life cycle, this regime sought to suppress the influence of the religious worldview and create a "socialist citizen". Three ceremonial opportunities: birth, marriage and death. represent the main line of the book's chapters. Since the publication offers an ethnological perspective, the attention focuses, apart from a retrospective analysis of the development of institutional ceremonies, on their reflection and acceptance by people. The knowledge basis of this book comes from ethnographic research conducted at various locations in Slovakia in several time segments - in the mid-1980s, at the beginning of the 1990s and subsequently in 2014-2016.